Sistem Informasi Pengolahan Data Nilai Siswa TK Dan SD Effata Shine Berbasis Web Di Kabupaten Rokan Hilir - Provinsi Riau - Elizabeth, Ivena; Marpaung, Noveri Lysbetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Effata Shine Kindergarten and Elementary School is located in Rokan Hilir District, Riau Province. To manage student grade, school still use manual method of recording on paper each student’s grade. So that not a few paper are lost due to slipping or even lost due to accidential wasted. This research aim to help the speed and quality of teacher in delivery of information as well as processing student grades and parents can monitor children’s grade and children’s attitude online. This information system uses the PHP programming language, HTML Javascript, MySQL and CSS Web Server for system design using XAMPP. Software system development is created using the waterfall method. Login menu design consisting of perents of students, homeroom teachers, subject teachers, and administrators have different access rights according to their respective interests. This system work to enter dan store data, student assessment and student final grade reports, so that it is easier to find out student grades that will be submitted by the school. This research resulted in a value processing information system that helps the work homeroom teachers and subject teachers in conducting the processing of value of students in order to manage value can be processed more efficiently and effectively, so that student's value information can be delivered well to parents online. System interface views are also created according to the existing report view so that the system can be used easily and generates accurate value calculations. Keywords: Information System, Student Grade, Student.